Application of hydrochemistry and residence time constraints to distinguish groundwater systems in the Karoo Basin prior to shale-gas exploration - Swana, Kelley (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.